COMMUNICATION STRATEGY OF DA’WAH IN ESTABLISHING SANTRI WITH QUR'ANIC CHARACTER AT THE INTERNATIONAL MUHAMMADIYAH BOARDING SCHOOL (IMBS) MIFTAHUL'ULUM PEKAJANGAN-PEKALONGAN - Budi, Agung Setyo; Praptiningsih, Novi Andayani (JOURNAL OF SCIENTIFIC COMMUNICATION (JSC), 2023)
In the era of globalization, various challenges are increasingly complex and massive. Therefore, in addition to the quality of a da'i , the da'wah communication that is built must be precise. So that the message conveyed can be received by mad'u in a comprehensive manner. This study aims to determine the da'wah communication strategy developed by IMBS Miftahul 'Ulum Pekajangan-Pekalongan in forming students with Qur'anic character so that they can contribute perspectives in research on communication science. This type of research is qualitative which emphasizes field research. Data collection methods used are interview, observation, and documentation methods. While the data analysis method used is descriptive qualitative analysis with the perspective of da'wah communication. Based on the results of the researcher's analysis, that by applying verbal and nonverbal da'wah communication strategies that emphasize habituation and exemplary methods. Santri are provided with special and general training which includes tahfidz cycles, khitobah as well as priest and qiro'at training . The reinforcement is using the principles of the nine golden habits which include; (1) Maintain prayer, including obligatory prayers in congregation and sunnah prayers, Tahajud and Dhuha . (2). Keeping the obligatory and sunnah fasts. (3). Zakat, infaq and sadaqah . (4) Reading Alqu'an ( One Day One Juz) and memorize Alqur'an ( One Day One Verse) . (5) Read a book at least one hour every day. (6) Islamic civilized in every activity. (7) Associating with pious people . (8) Do good deeds and provide benefits to others. (9) Say positive and smile. The conclusion in the field, the da'wah communication strategy in applying the Qur'anic character to the students, when researching it on a long-term basis turned out to produce quite significant results. This can be proven by the large number of alumni who become lecturers, community leaders, and educators in the community. as well as educational institutions. However, there is also practice in the implementation of the field that is less than optimal, especially for young asatiz who are less competent and unable to set an example because from this golden habit there are actually quite a few asatiz who do not practice especially in the realm of sunnah. In terms of literacy, it is not yet representative when referring to the principles of the digitalization era with its international brand, as well as Arabic and English are not yet the main languages, even though to become students with Qur'anic character requires comprehensive language fluency in order to be able to understand the Qur'an independently and productively.